PENGARUH KINERJA KEUANGAN TERHADAP NILAI PERUSAHAAN DENGAN MEKANISME GOOD CORPORATE GOVERNANCE SEBAGAI VARIABEL MODERASI - Arief maulana nst; Zulbahridar '; Hariadi ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
This study aims us to determine the effect of the financial performance of the company's value by moderating variables: Good Corporate Governance is proxied by managerial ownership, institutional, and the audit committee. This study that are used the capture technique purposive sampling. The type of data that writers use in this research is secondary data. Samples are automotive companies listed in the Indonesia Stock Exchange (BEI) in 2010 - 2014. Testing this hypothesis using multiple regression using SPSS version 18.00. This study shows the results that good corporate governance proxied by managerial ownership, institutional ownership, and the audit committee are jointly able to moderate influence on the value of the company 's financial performance. In addition, this study also showed results that ROE significant positive effect on Tobin 's Q.Keywords : Financial Performance, Value Company and Good Corporate Governance